2020
DOI: 10.1002/epi4.12399
|View full text |Cite|
|
Sign up to set email alerts
|

EEG findings in acutely ill patients investigated for SARS‐CoV‐2/COVID‐19: A small case series preliminary report

Abstract: Objective: Acute encephalopathy may occur in COVID-19-infected patients. We investigated whether medically indicated EEGs performed in acutely ill patients under investigation (PUIs) for COVID-19 report epileptiform abnormalities and whether these are more prevalent in COVID-19 positive than negative patients. Methods: In this retrospective case series, adult COVID-19 inpatient PUIs underwent EEGs for acute encephalopathy and/or seizure-like events. PUIs had 8-channel headband EEGs (Ceribell; 20 COVID-19 posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(188 citation statements)
references
References 31 publications
9
160
4
7
Order By: Relevance
“…Galanopoulou et al [ 63 ] studied 28 individuals suspected of COVID-19. Twenty-two were tested positive for SARS-CoV-2.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…Galanopoulou et al [ 63 ] studied 28 individuals suspected of COVID-19. Twenty-two were tested positive for SARS-CoV-2.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…One small study of 22 patients with confirmed COVID-19 showed that the most common indications for EEG were new-onset encephalopathy and seizure-like events. Sporadic epileptiform discharges were present in 41% of the patients [8]. It is recommended to perform a continuous EEG monitoring in a patient who is in a critical medical condition, including those with COVID-19, and has a change in mental status to make sure that NCSE is not a part of the clinical scenario [9].…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI revealed non-specific white matter hyperintensities, ruling out structural lesions which could justify neurological manifestations. The altered mental status might have been caused also by non-convulsive status epilepticus, a clinical condition already associated with COVID-19 (Le Guennec et al, 2020), yet was excluded by the EEG, which showed diffuse slowing with frontal sharp waves, a finding frequently reported in COVID-19-related encephalopathy (Galanopoulou et al, 2020;Pasini et al, 2020). Aphasia was accompanied by manifestations consistent with dysexecutive syndrome and behavioral symptoms, suggesting a frontal lobe dysfunction.…”
Section: Discussionmentioning
confidence: 89%